EQUIPMENT COMPOSITION OPTIMIZATION OF A MULTI-PROFILE TRAINING COMPLEX BASED ON WIRELESS COMMUNICATION - Morzhov, Volodymyr; Zhukov, Igor (Proceedings of National Aviation University (archive), 2019)
Purpse: The problems of the equipment composition optimizing in a multi-profile training center are considered. The structure of such center includes several complex and specialized aircraft simulators of various aircraft types, both civil and military. Operational changes in the composition of equipment allow for the rational structure of the equipment and reconfigurable simulator structure, which is necessary for a pilot training technical support of a certain aircraft type. It has been shown that it is necessary to use the wireless network to complete this task. Using such network as part of simulator complex allows providing wireless transmission of data streams between separate simulators of training complex simulators. . Such information transfer organization between separate devices of simulators allows excluding from the equipment of simulators the expensive cables from electrical wires that were previously used to transmit information flows as the electrical signals between separate devices of simulators. Using the wireless network for information flows transmit in flight simulators will significantly increase the efficiency of training equipment use using for aircraft pilots training.